Geographies of Memory: Ruth Beckermann's Film Aesthetics - Karen Remmler (Studies in 20th & 21st Century Literature, 2007)
How might we view the films by the Jewish Austrian filmmaker, Ruth Beckermann through the lens of the prose by the late German writer W.G. Sebald? The archival and, at the same time, haunting prose of Sebald's works such as The Emigrants or Austerlitz bears a close resemblance to the work of memory that Beckermann's films begs us to do. By focusing on particular spaces of remembrance in Beckermann's films in comparison to Sebald's similar practice of intermeshing historical and individual memories, this essay explores how the gendered construction of cultural memory takes place through transcultural encounters with those deemed as Other. Even as locations in Beckermann's films—a living room, the interior of a train passing through Vienna, a cold and sterile exhibit space, or a dream-like landscape—exist in reality, Beckermann's situating of memory in them, creates other, more compelling encounters between the living and the dead. The gendering of memory sites in Beckermann's films creates an alternative to the more elegiac images that are conjured in Sebald's textual and visual spaces of remembrance.
Keywords: Jewish Austrian filmmaker; Ruth Beckermann; Jewish; Austria; Austrian; Film; W.G. Sebald; The Emigrants; Austerlitz; rememberance; memory; historical memory; individual memory; gender; gendered memory; other; transcultural; space